2022
DOI: 10.3390/computers11120168
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Mohammad et al. User Authentication and Authorization Framework in IoT Protocols. Computers 2022, 11, 147

Abstract: The authors wish to make corrections to change the authorship [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…Effective strategy formulation involves aligning organizational goals with market opportunities and competitive advantages, which can impact financial metrics through improved resource allocation, innovation, and market positioning (Mashingaidze and Chinakidzwa, 2021). Non-financial performance measures, such as stakeholders' satisfaction and employee engagement, are positively influenced when the formulated strategy addresses stakeholders' needs and aligns with the organization's values (Mohammad, et al, 2019). However, the lack of significance in the relationship between strategy implementation and performance could be attributed to factors like implementation challenges, unforeseen external influences, and the complexity of translating formulated strategies into actionable operational plans (Njagi and Kombo, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective strategy formulation involves aligning organizational goals with market opportunities and competitive advantages, which can impact financial metrics through improved resource allocation, innovation, and market positioning (Mashingaidze and Chinakidzwa, 2021). Non-financial performance measures, such as stakeholders' satisfaction and employee engagement, are positively influenced when the formulated strategy addresses stakeholders' needs and aligns with the organization's values (Mohammad, et al, 2019). However, the lack of significance in the relationship between strategy implementation and performance could be attributed to factors like implementation challenges, unforeseen external influences, and the complexity of translating formulated strategies into actionable operational plans (Njagi and Kombo, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…With the exceptions of studies such as these most study confirm the positive effect and influence of strategy formulation on performance. Such is the case with Mohammad, et al, (2019) who indicated that formulation of good strategy improved performance of small and medium size enterprise.…”
Section: Independent Variablementioning
confidence: 97%